Orthographic effects on L2 production and L2 proficiency in ESL learners with non-alphabetic and orthographically opaque L1. (6th November 2022) - Deng, Wenxiyuan; Chan, Kit Ying; Au Yeung, Ka Man
Abstract: This study examined the role of first language (L1) transparency in intra-orthographic effects on second language (L2) pronunciation by studying L2 learners with a non-alphabetic and orthographically opaque L1 and an alphabetic L2. Relations between orthographic effects, phonological awareness, and L2 proficiency were examined. Fifty-four Cantonese-speaking English as a second language (ESL) learners participated in Experiment 1 with orthographic effect tasks (homophone and silent-letter read-aloud) and phonological awareness tasks. Thirty Cantonese-speaking and 30 Mandarin-speaking ESL learners participated in Experiment 2 with orthographic effect tasks and an L2 proficiency task. The L2 pronunciation of Cantonese and Mandarin participants was subjected to intra-orthographic effects. Phonological awareness and L2 proficiency were associated with less orthographic effects on L2 pronunciation in Cantonese participants. Mandarin participants did not subject to more orthographic effects than Cantonese participants when controlling L2 proficiency, implying that shared alphabetic scripts between Pinyin and English did not interfere with L2 production. Overall, transferring the L1 reading strategy that relies on orthography to decode phonology to L2 reading seemed not to be the key mechanism behind intra-orthographic effects. L2 graphemes were likely to be decoded with incorrect L2 grapheme-to-phoneme correspondences, resulting in intra-orthographic effects.